The investment of Waqf Sunni in Iraq in the light of experience of Johor, Malaysia: An analytical study / Intisar Abduljabbar Mostafa - Intisar Abduljabbar, Mostafa (2017)
The study examines the investment of the Sunni endowment of Iraq. This is a comparative analytical research in view of the endowment experience of Johor, Malaysia. The study aims at achieving the following objectives: discerning the legal ruling of endowment in Islamic jurisprudence and that it is legally valid and binding and its ownership belongs to the donor (waqif). The study also examined the important relationship between the (waqf) and its investment. It highlighted the rules governing the investment of endowment in Iraq as well as its management. In many respects the investments of endowment assets in Iraq remain traditionally historic including exchange contracts and endowment assets’ renting contract. Means of external investment include share-cropping contract, irrigation contract, land leasing contract, and farm yield leasing contract. All these commercial contracts remain traditional and there was no development in the investment universe even though there exist varied modern investment tools for the development of Islamic endowments. The study also illuminated the relationship between Sunni endowments and other governmental agencies and discussed the negative impact of such agencies on the management of the endowments. The study also analyzed the governance of endowments and the internal regulation statutes which are a major cause in the decline of the endowment sector over the past decades. The study investigated the investments of endowments in the state of Johor with the aim of exploring its advantages to improve the management and performance of the Sunni endowment in Iraq. The research used the inductive analytical methodology which relies on library sources as well as the applied methodology of field study of the Sunni endowment of Iraq and the State of Johor endowments. The field studies were carried out through personal interviews with senior staff and managers in various endowment institutions in Baghdad and Johor. The study concludes that: The primary reasons which led to the decline of endowments assets in Iraq and have impeded its development and caused it to be subject to considerable criticism and complaints are mismanagement, flawed investment practices, and the absence of official authority exercising adequate regulatory supervision. On the other hand and quite in contrast, the Malaysian endowment experience represented by Johor is enriching and fruitful in terms of achieving its charitable objectives. It is constantly developing with a noticeable improvement of its service delivery and effectiveness. Those who are managing the Johor endowments have been playing a significant role in development the performance of endowments in Malaysia. Those results have been achieved clearly on the basis of the planned reforms intended for the endowment sector in Malaysia, which were put into practice. The endowment success rates that have been achieved were part of the overall strategy aimed at improving the role of endowments and raising the productivity level of its institutions. Muslims in Malaysia have been able to preserve the essence of Islam and its legal provisions for endowments, while simultaneously maintaining a strong and effective drive for future development and progress.